Fixed Points of the Mathematical Configuration of Mass and Energy. - Cameron, Vinoo; Otter, Theo Den (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
This is a complex mathematics delineating the curvature of the universe and the curvature between absolute motion and absolute inertia. The complex equation for the curve is as follows followed by the prime number sieve.